2017
DOI: 10.1007/s00709-017-1197-6
|View full text |Cite
|
Sign up to set email alerts
|

Resin secretory canals in Protium heptaphyllum (Aubl.) Marchand. (Burseraceae): a tridimensional branched and anastomosed system

Abstract: Protium heptaphyllum is a Burseraceae species known by the production of aromatic resin with medicinal, economic, and ecological values. Information on the development, architecture, and lifetime of the secretory system are crucial to understand the resin production and contribute to a more sustainable tapping regime. We investigated the histology and ultrastructure of the secretory canals under a developmental point of view. Stem samples were analyzed under light and transmission electron microscopy by conven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
1
15
0
1
Order By: Relevance
“…Our results show that the histochemical and TEM analyses show that the epithelium and parenchymatous sheath of ducts and cavities act as production sites of hydrophilic and lipophilic secretions. Previous studies have reported that the epithelium and parenchymatous sheath act as secretion production sites (Rodrigues et al, 2011a,b;Leite et al, 2014;Palermo et al, 2018). The ultrastructure of epithelial cells shows that the secretion is externalized to the lumen by the eccrine mechanism, corroborating the study of Leite et al (2019).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Our results show that the histochemical and TEM analyses show that the epithelium and parenchymatous sheath of ducts and cavities act as production sites of hydrophilic and lipophilic secretions. Previous studies have reported that the epithelium and parenchymatous sheath act as secretion production sites (Rodrigues et al, 2011a,b;Leite et al, 2014;Palermo et al, 2018). The ultrastructure of epithelial cells shows that the secretion is externalized to the lumen by the eccrine mechanism, corroborating the study of Leite et al (2019).…”
Section: Discussionsupporting
confidence: 75%
“…Epithelial cells with thin, disorganized walls, a winding plasma membrane, vacuolization, low-density peripheral cytoplasm with little osmiophilic material, few organelles and mitochondria and numerous vesicles adhered to the membrane are evidence that secretory cells do not present an intense secretory process, as observed in duct and cavity-secreting epithelial cells in the literature (Franco & Albiero 2018;Palermo et al, 2018;Leite et al, 2019;Haratym et al, 2020). However, our results corroborate Peng et al (2012) and Turner & Lange (2015) when describing ultrastructural characteristics of cavities in adult tissue, and in part with results of Lacchia & Carmello-Guerreiro (2009) for epithelial cells of secretory ducts of Anacardiaceae in the senescent stage.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Throughout history, plant resins have been, among others, widely used for embalming, for religious rites and for various medical purposes (Langenheim, 2003). Emulsions, rich in terpenoids and mucilage, are produced in structures known as secretory ducts, and they play important roles in deterring herbivores and pathogens (Palermo et al, 2018). Despite advances in our knowledge concerning resin duct structure, secretory processes, and resin composition, many aspects still require in-depth investigations, especially among tropical species.…”
Section: Introductionmentioning
confidence: 99%
“…The study of distribution patterns of resiniferous ducts within those structures, which vary greatly among species, will be important for elucidating their ecological roles and defining strategies for commercial resin harvesting. Cytological evaluations, in turn, are essential for understanding the processes involved in resin production, as the cellular machinery required and the dynamics of the secretory processes are directly related to the chemical nature of the emulsions produced (Setia et al, 1977; Bhatt, 1987; Nair & Subrahmanyam, 1998; Palermo et al, 2018). Ontogenetic studies are also needed to define the structural type of the resin duct, as they can develop from lysis and/or from cell separation.…”
Section: Introductionmentioning
confidence: 99%